2002
DOI: 10.1093/ageing/31.6.445
|View full text |Cite
|
Sign up to set email alerts
|

Slicing the health service cake: the Islington study

Abstract: Carers give compensatory care rather than act as bridges to link people with dementia with the health care system. People with dementia need advocates. Older people with depression are high users of all services. They remain under-treated pharmacologically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
5
11
0
Order By: Relevance
“…The findings show that people with early-stage dementia were thought to have a range of complex needs which remained largely unmet, which was consistent with findings of previous studies (Nelson et al, 2002;Toseland et al, 2002). These needs were thought to be even more likely to be unmet for people with dementia from minority groups, which again has been documented in previous research Harvey, 1998;Keady & Nolan, 1997;Royal College of Psychiatrists, 2000).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings show that people with early-stage dementia were thought to have a range of complex needs which remained largely unmet, which was consistent with findings of previous studies (Nelson et al, 2002;Toseland et al, 2002). These needs were thought to be even more likely to be unmet for people with dementia from minority groups, which again has been documented in previous research Harvey, 1998;Keady & Nolan, 1997;Royal College of Psychiatrists, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…Despite this growing need for early intervention for people with dementia, it is still unclear what factors increase the likelihood that people with dementia and their carers will engage with services. Some research indicates that people with dementia may access services less often than their counterparts who do not have dementia (Nelson et al, 2002;Toseland et al, 2002), although studies have shown contradictory findings, with some reporting that people with dementia have more contact with services than people with other forms of impairment (Eaker et al, 2002;Moriarty, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional community survey in the UK, The Islington Study, found that people with dementia used less health services than non-demented. The presence of a co-residing informal carer predicted less use of social services but no increase in health service consultations and the researchers therefore concluded that carers act as providers of compensatory rather than supplementary care (Nelson et al, 2002). Our findings indicate that informal care substitute rather than compliments formal care.…”
Section: Discussionmentioning
confidence: 47%
“…Depression in AD is associated with other neuropsychiatric symptoms and impairment in activities of daily living (Lyketsos et al, 1997). It increases caregiver burden and economic costs, including earlier institutionalisation (Steele et al, 1990;Livingston et al, 1997;Brodaty and Luscombe, 1998;Gonzalez-Salvador et al, 1999;Wolstenholme et al, 2002;Nelson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%